Monetary-fiscal interaction and quantitative easing - Josef Hollmayr; Michael Kühl (Deutsche Bundesbank, 2018)
This paper analyzes the monetary-fiscal interaction if the central bank conducts quantitative easing. Although asset purchases have similar effects on the real economy under monetary and fiscal dominance, wealth effects yield a qualitatively different response on the rate of inflation. Our results show that under fiscal dominance, unconventional monetary policy has similar effects to conventional monetary policy on inflation because these wealth effects exert downward pressure on prices. The longer the average maturity, the more volatile is the transmission of quantitative easing to the real economy.
Keywords: E32; E44; E62; 330; Monetary Policy; Fiscal Policy; Asset Purchase Program